PASSENGER PERFORMANCE ANALYSIS IN SENAYAN MRT JAKARTA PLATFORM DURING COVID-19 PANDEMIC USING MICROSIMULATION - Harsono, Keza
Since March 2020, Corona Virus Disease 2019 (COVID-19) has spread rapidly in Indonesia. In a public facility, health protocol must be implemented, including physical distancing. The implementation of physical distancing at a train station as a public facility can be analyzed through a microsimulation model with PTV VISSIM software, with the performance indicator of distance between passengers. The study location of the microsimulation model is MRT Senayan Jakarta Platform, with the calibration of passenger walking behavior and the validation against the passenger walking characteristics based on a survey in the existing pandemic conditions. The microsimulation model is analyzed on the existing condition during pandemic and the scenarios of maximum passenger flow with alternative policy changes. Based on the microsimulation results in existing conditions, the distance between passengers is far greater than the required distance, indicating the physical distancing implementation. In the scenario of maximum passenger flow, the average distance between passengers is smaller than the required distance. Alternative policy changes are needed to this scenario. Based on the microsimulation results, reducing headway, increasing train capacity, increasing train door duration, and changing train door function can improve the distance between passenger performance to reduce the virus spreading at stations in crowded passenger conditions. Changing the train door function will be effective if it is applied to the uncrowded conditions or applied with the other changes of policy alternatives.